2018
DOI: 10.4171/dm/634
|View full text |Cite
|
Sign up to set email alerts
|

On Exact Pleijel's Constant for Some Domains

Abstract: We provide an explicit expression for the Pleijel constant for the planar disk and some of its sectors, as well as for N -dimensional rectangles. In particular, the Pleijel constant for the disk is equal to 0.4613019 . . . Also, we characterize the Pleijel constant for some rings and annular sectors in terms of asymptotic behavior of zeros of certain cross-products of Bessel functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The value of the Pleijel constant for a given domain is generally unknown. Bobkov [3] calculated Pl(Δ 𝐷 Ω ) for some simple domains, including the Euclidean disk in ℝ 2 . When Ω = 𝔹 is a Euclidean disk in ℝ 2 , he showed that Pl(Δ 𝐷 𝔹 ) = 0.461 ⋯…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of the Pleijel constant for a given domain is generally unknown. Bobkov [3] calculated Pl(Δ 𝐷 Ω ) for some simple domains, including the Euclidean disk in ℝ 2 . When Ω = 𝔹 is a Euclidean disk in ℝ 2 , he showed that Pl(Δ 𝐷 𝔹 ) = 0.461 ⋯…”
Section: Introductionmentioning
confidence: 99%
“…The value of the Pleijel constant for a given domain is generally unknown. Bobkov [3] calculated prefixPlfalse(ΔΩDfalse)$\operatorname{Pl}(\Delta _\Omega ^{D})$ for some simple domains, including the Euclidean disk in double-struckR2$\mathbb {R}^2$. When normalΩ=double-struckB$\Omega ={{\mathbb {B}}}$ is a Euclidean disk in double-struckR2$\mathbb {R}^2$, he showed that prefixPlfalse(ΔBDfalse)=0.461$\operatorname{Pl}(\Delta _{{\mathbb {B}}}^{D})=0.461\cdots$…”
Section: Introductionmentioning
confidence: 99%